Platelet Limphocyte Ratio and Procalcitonin in Survivor and Non-Survivor Sepsis Patients at Dr. Wahidin Sudirohusodo Hospital Makassar - Fitriana, Astri Yul; Nurulita, Asvin; Bahrun, Uleng; Arifin Seweng (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2025)
Sepsis is a life-threatening organ dysfunction caused by dysregulation in the host's response to infection and is a major cause of global morbidity and mortality.The platelet-to-lymphocyte ratio (PLR) is considered a prognostic marker of sepsis. Another inflammatory marker, procalciton in which is secreted in response to bacterial endotoxin can also serve as a biomarker for diagnosis, prognosis and monitoring of sepsis patients. Analysis of platelet lymphocyte ratio and procalcitonin levels may therefore be useful for predicting survival outcomes in sepsis. This retrospective observational study included 276 patients diagnosed with sepsis, consisting of 128 survivors and 148 non-survivors. Statistical analysis was performed using the Kolmogorov-Smirnov test, Mann-Whitney test, Spearman correlation test, and Friedman test, with significance defined as p <0.05. No significant differences in mean platelet-to lymphocyte ratio between a survivors and non-survivors on day 1 (200.59 vs 233.91, p >0.05), day 3 (191.58 vs 238.74, p >0.05), or day 5 (210.42 vs 208.62, p >0.05). Similarly, no significant difference in mean procalcitonin levels was found on day 1 (20.18 ng/mL vs 16.20 ng/mL, p >0.05). However, mean procalcitonin levels were significantly lower in survivors compared with non-survivors on day 3 (14.04 ng/mL vs 17.48 ng/mL, p <0.05) and day 5 (7.78 ng/mL vs 23.06 ng/mL, p <0.05). In survivors, procalcitonin levels showed a significant decreasing trend across days 1, 3, and 5 (p <0.05). There was no difference in platelet-to-lymphocyte ratio values between survivors and non-survivors. There was a significant difference in procalcitonin levels between survivors and non-survivors on the third and fifth days.